Media Scrabble Word dalam Penguasaan Kosakata Bahasa Jerman - Hijra Hijra; Hasmawati Hasmawati (Universitas Negeri Makassar, 2024)
Abstract. The purpose of this study is to determine the improve in the mastery of German vocabulary using Scrabble Word media in the class X SMAN 11 Enrekang, Enrekang Regency, South Sulawesi. This type of research is Classroom Action Research which consists of two cycles and each cycle concists of four stages such as planning, implementation, observation,and reflection. The subjects in this study were students of X grade, with 28 person. The type of data in this study consists of qualitative and quantitative data. Qualitative data were obtained through obsevation and quantitative data obtained through the results vocabulary mastery test, in cycle I and cycle II . from the German vocabulary mastery test, student got an average score 55,35 in the first cycle and increase in the second cycle with an average score of 86,78 . It the concluded that the using of Scrabble Word media in learning can improve student’s German vocabulary class X SMAN 11 EnrekangKeywords: Class Action Reaearch, Vocabulary, Scrabble Word, German